Numerical Study on the Behaviour of Built-up Cold-Formed Steel Corrugated Web Beams End Connections - Ioan Both; Mircea Burca; Stefan Benzar; Viorel Ungureanu (Civil Engineering Journal, 2023)
Corrugated web beams made of cold-formed steel components represent an economical solution for structures, offering high flexural capacity and deformation rigidity. For conventional corrugated web beams, made of thick plates for the flanges and thin sinusoidal steel sheets for the web, the elements can be joined by standard bolted end-plate connections. In the case of corrugated web beams made of thin-walled cold-formed steel components only, additional plates are required to accommodate the shape and position of the profiles. A large experimental program was carried out on corrugated web beams made of cold-formed steel elements. One of the objectives was to determine the capacity of these beams and the influence of several parameters on the response of the beam, but also very important were the end connections of these beams. The recordings obtained from the tests were used to validate a numerical model. Based on the validation of the numerical model, finite element analyses were performed to study four solutions for end connections to facilitate assembly, optimise the number of bolts, and increase the capacity and rigidity. Although the connection can be improved for assembling reasons with the presented solutions, the overall capacity is limited by the components subjected to compression that lose their stability. Doi: 10.28991/CEJ-2023-09-04-01 Full Text: PDF